A Population based Study on Self Medication Practice in Pakistan - Kamran Khan; Aqsa Zaman; Furqan Khurshid Hashmi; Rizwan Khan (مجله كليه طب الكندي, 2022)
Background: The risk of antibiotics resistance (AR) increases due to excessive of antibiotics either by health care provider or by the patients.